PPARβ/δ Agonist Alleviates Diabetic Osteoporosis via Regulating M1/M2 Macrophage Polarization - Chen, Miao; Lin, Weimin; Ye, Rui; Yi, Jianru; Zhao, Zhihe (Frontiers in Cell and Developmental Biology, 2021)
Diabetic osteoporosis is a common complication in diabetic patients, leading to increased fracture risk and impaired bone healing. As a member of the peroxisome proliferator-activated receptor (PPAR) family, PPARβ/δ agonist is suggested as a therapeutic target for the treatment of metabolic syndrome, and has been reported to positively regulate bone turnover by improving osteogenesis. However, its regulatory role in diabetic osteoporosis has not been reported yet. Here, we explored the therapeutic effects and potential mechanisms of PPARβ/δ agonist to the osteoporotic phenotypes of diabetic mice. Our results indicated that the osteoporotic phenotypes could be significantly ameliorated in diabetic mice by the administration of PPARβ/δ agonists. In vitro experiments suggested that PPARβ/δ agonist treatment could alleviate the abnormal increase of osteoclast activity in diabetic mice by rectifying high glucose-mediated macrophage dysfunction instead of directly inhibiting osteoclast differentiation. Mechanistically, Angptl4 may act as a downstream target of PPARβ/δ to regulate macrophage polarization. In conclusion, our study demonstrates the potential of PPARβ/δ agonist as a therapeutic target for the treatment of osteoporosis and immune homeostasis disorder in diabetic patients.